How Home-Peers Affect the Export Market Exit of Small Firms: Evidence From Canadian Exporters - Sui, Sui; Baum, Matthias; Malhotra, Shavin (Entrepreneurship Theory and Practice, 2019)
We investigate how home-peer entry density (the number of same-industry firms that originate from the same country and export to the same foreign market) affects the export market exit of small firms. Drawing on panel data from 41,445 Canadian small business exporters, we find a U-shaped relationship between home-peer entry density and small firms’ hazard of exit from an export market; that is, firms’ hazard of exit decreases as the home-peer density increases to a certain point and increases after that point. We also find that this U-shaped relationship is stronger for small firms that internationalize early.